1990
DOI: 10.3382/ps.0692134
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to Pasteurella multocida in Protein-Deficient Chickens

Abstract: Studies were conducted to determine the effects of dietary protein restriction on the humoral immunity (HI) and cell-mediated immunity (CMI) of chickens. New Hampshire chickens were separated into two dietary treatment groups: basal, containing 3,200 kcal/kg and 21% protein; or protein restricted (PR), containing 3,200 kcal/kg and 7% protein. In studies involving HI, half of the birds in each dietary treatment were vaccinated against fowl cholera at 4 and 8 wk of age. Blood samples were collected weekly beginn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…The results indicated that depression of dietary CP level from 18% to 14% gave harmful effects on the secondary lymphoid tissue. These phenomena were confirmed by Payne et al. (1990) and Kenney et al.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The results indicated that depression of dietary CP level from 18% to 14% gave harmful effects on the secondary lymphoid tissue. These phenomena were confirmed by Payne et al. (1990) and Kenney et al.…”
Section: Discussionsupporting
confidence: 56%
“…ND‐titre of hens fed 18% CP diet was significantly higher than that of hens fed 14% CP. Accordingly, Payne et al. (1990) reported that susceptibility to Newcastle disease virus was increased dramatically in protein‐deprived chicks and serum antiviral antibody responses were also reduced.…”
Section: Discussionmentioning
confidence: 99%
“…However, significant effects of dietary protein and amino acids levels on bird immunity have been reported (Kidd, 2004). Payne et al (1990) reported that the feeding with very low protein diets had negative effects on cellular immunity of birds. Significant interactions between additives and protein levels were not observed for antibody response to Newcastle disease.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that deficiency or excess of dietary protein (Glick et al, 1981(Glick et al, , 1983Payne et al, 1990) or amino acids (Bhargava et al, 1970(Bhargava et al, , 1971Tsiagbe et al, 1987aTsiagbe et al, , 1987b) alters immune responses. BCAA have been shown to play very important roles in the immune organ development (Kidd, 2004).…”
Section: Discussionmentioning
confidence: 99%